2006
DOI: 10.1017/bjn20061912
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inulin supplementation of diets with or without hydrolysed protein sources on digestibility, faecal characteristics, haematology and immunoglobulins in dogs

Abstract: Dogs with food allergy are often treated by giving a diet with hydrolysed protein sources. Prebiotics might also be successful in prevention and treatment of allergic disease through their effect on the colonic microflora, analogous to studies on probiotics in allergic children. The present study was set up to investigate the effect of supplementing inulin (IN) to commercial hypoallergenic dog diets on apparent nutrient digestibility, faecal characteristics, haematology and Ig in dogs. Supplementation of 3 % I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 59 publications
8
37
0
1
Order By: Relevance
“…As inulin has a higher degree of polymerization compared with OF, Hesta et al (2001) suggested a slower fermentation of inulin in the relatively short colon of cats. Verlinden et al (2006) also reported that inulin supplementation did not affect faecal pH in adult dogs. We suggested that inulin supplementation had no consistent effect on faecal pH in the current study as there was no difference in faecal pH on day 21 between groups, whereas EG had a lower faecal pH than CG on day 14 and 28 ( Table 2).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As inulin has a higher degree of polymerization compared with OF, Hesta et al (2001) suggested a slower fermentation of inulin in the relatively short colon of cats. Verlinden et al (2006) also reported that inulin supplementation did not affect faecal pH in adult dogs. We suggested that inulin supplementation had no consistent effect on faecal pH in the current study as there was no difference in faecal pH on day 21 between groups, whereas EG had a lower faecal pH than CG on day 14 and 28 ( Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…This effect is strictly related to dose of fructans (Saavedra, 2005). Verlinden et al (2006) reported that inulin supplementation lowered faecal score (loose faeces) in adult dogs but the decrease in faecal score had no clinical importance because it remained in an acceptable range and was not associated with diarrhoea. In our study, a lower faecal score would indicate formation of softer faeces and the dose of inulin supplemented to the kids in EG did not adversely affect faecal score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations